THE IMPLEMENTATION OF FISHBOWL TECHNIQUE IN TEACHING REPORT TEXT: WAYS TO ACTIVATE STUDENTS’ SPEAKING PERFORMANCE (RETAIN, 2017)
THE IMPLEMENTATION OF FISHBOWL TECHNIQUE IN TEACHING REPORT TEXT: WAYS TO ACTIVATE STUDENTS’ SPEAKING PERFORMANCE Ratna Rohmawati English Language Teaching, Language and Art Faculty, State University of Surabaya ratnarohmawati2705@gmail.com Nur Chakim, S.Pd., M.Pd English Language Teaching, Language and Art Faculty, State University of Surabaya Abstract Language is one of the communication tools that should be spoken. In this era, English is important to master in order to communicate to the outside world. In communication, speakers must use gestures and sounds to make the listener understand what is said. As known, speaking has actually been taught since in the early age. However, many students still feel afraid to speak English in front of the class. They are afraid to do so because they do not know the vocabulary and they feel shame in making mistakes when speaking. From these, the researcher aimed to observe the students’ performance when they are taught speaking by using more interesting technique. The technique used in this study is called Fishbowl discussion which is suitable to be applied in a class with many students as it gives chance to every student to talk. This study used descriptive-qualitative design. The subjects were junior high school students in SMPN 1 Patianrowo, especially the 9F students. To collect the data, the instruments used were field-notes and speaking rubric. The field-notes is used to collect the data during the observation of the teaching learning process while speaking rubric is used to collect the data of students’ speaking performance. After the data had been collected, they were further analyzed based on qualitative analysis theory from Ary, et al. (2010). Aside, report text was chosen as it contains some topics that can be discussed based on reality and existing information. The results of this study showed that teacher who teach speaking by using more interesting technique will make the students more comfortable in speaking and also will trigger them to be more active. Using this technique, the students were less afraid to speak because they may say anything freely without any compulsion and pressure from the teacher. Keywords: speaking, Fishbowl, classroom discussion, active students, and report text. Abstrak Bahasa adalah salah satu alat komunikasi yang seharusnya diucap. Saat ini, bahasa inggris sangatlah penting untuk dikuasai agar dapat berkomunikasi dengan dunia luar. Dalam berkomunikasi, pembicara harus menggunakan gestur dan suara supaya pendengar menangkap apa yang dibicarakan. Telah diketahui bahwa bahasa Inggris telah dipelajari sejak dini. Namun, siswa masih saja merasa takut untuk berbicara bahasa inggris di depan kelas. Mereka takut karena tidak tau kosakata dalam bahasa inggris serta malu apabila membuat kesalahan saat berbicara. Oleh karenanya, peneliti membuat meneliti bagaimana kemampuan berbicara siswa setelah diajarkan speaking dengan Teknik yang lebih menarik. Teknik yang dipakai di sini adalah diskusi fishbowl yang sangat cocok digunakan di sebuah kelas dengan siswa yang banyak. Teknik ini juga memberikan kesempatan pada tiap siswa untuk berbicara. Desain penelitian yang digunakan adalah deskripsi kualitatif. Subjek pada penelitian ini adalah siswa 9F di SMP Negeri 1 Patianrowo. Instrumen yang digunakan untuk mengumpulkan data adalah catatan lapangan dan rubric kemampuan berbicara. Catatan lapangan digunakan untuk mengumpulkan data dari hasil pengamatan selama proses pembelajaran sedangkan rubrik kemampuan berbicara digunakan untuk melihat kemampuan siswa dalam berbicara. Setelah data terkumpul, data akan dianalisis dengan teori analisis data dari Ary, et al. (2010). Teks yang digunakan dalam penelitian ini adalah teks report karena topik dalam teks ini dapat didiskusikan sesuai kenyataan dan informasi yang ada. Hasil dari peneitian ini menunjukkan bahwa guru yang mengajar dengan menggunakan teknik yang menarik akan membuat siswa lebih nyaman dalam berbica juga akan membuat siswa lebih aktif dalam berbicara. Dengan menggunakan tekni ini, siswa menjadi lebih berani mengungkapkan apa yang dipikirkan tanpa adanya paksaan dan tekanan dari guru. Kata kunci: berbicara, Fishbowl, diskusi kelas, siswa aktif, dan teks report.